Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2008)
Low-Dose Mitomycin C as a Prophylaxis for Corneal Haze in Myopic Surface Ablation Thornton I, Puri A, Xu M, Krueger RR Am J Ophthalmol 2007; 144: 673-81. Incidence of cataract surgery from 1980 through 2004: 25-year population-based study Erie JC, Baratz KH, Hodge DO, Schleck CD, Burke JP J Cataract Refract Surg 2007; 33: 1273-7. Outcomes of radiofrequency in advanced keratoconus Lyra JM, Trindade FC, Lyra D, Bezerra A J Cataract Refract Surg 2007; 33: 1288-95. Intracorneal rings for keratoconus and keratectasia Ertan A, Colin J J Cataract Refract Surg 2007; 33: 1303-14.